The relationship between financial development and the cost of capital: evidence from Sub-Saharan Africa - Tshivhase, Tshidzani Thusanani (My University, 2020)
This study aims to provide evidence of the relationship between financial development and the cost of capital in Sub-Saharan Africa (SSA) using a panel of 5 countries (Kenya, Mauritius, Namibia, Nigeria and South Africa) from 2011 to 2016. The variables used as proxies for Financial Development were stock market development and banking sector development. Using a Panel Least Squares Regression, the estimation results show that stock market development reduces the cost of capital and that this is achieved by greater diversification of risk, access to quality information and reducing monitoring and transaction costs. Conversely, the study finds that banking sector development weakly reduces the cost of capital in SSA due to the relatively low levels of banking sector competition experienced. It follows that low bank competition reduces the effectiveness of such institutions in fulfilling their functions as financial intermediaries. The significance of this study is mainly on the potential influence that such insights have on policy makers designing financial policies which will aid in attracting greater investment to the region at a desirable cost.
A research report submitted in fulfilment of the requirements for the degree of Masters of Management in Finance and Investment (MMFI) to the Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, 2020